1996
DOI: 10.1039/ft9969204843
|View full text |Cite
|
Sign up to set email alerts
|

Structure of alumina surfaces

Abstract: The structure of hydroxylated alumina surface is analysed by IR spectroscopy. The variety of OH groups differing in number and coordination of surrounding metal atoms, for the completely hydrated surface, either formed by ideal low-index planes, or complicated by crystal edges and corners or cation vacancies, is restricted to six, but grows dramatically upon dehydroxylation. The results account for the complex structure observed previously in the IR spectra of surface OH groups after high-temperature treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
210
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(226 citation statements)
references
References 27 publications
15
210
1
Order By: Relevance
“…This loss of water during the reaction is also seen as a negative band in the area around 3200 cm −1 . The loss of different types of free OH groups at the surface is evidenced as a small negative band at 3700 cm −1 (not shown in figure) (Tsyganenko and Mardilovich, 1996). When SO 2 is introduced simultaneously with NO 2 the bands of nitrate are still dominant, especially when the ratio of SO 2 to NO 2 is low, cf.…”
Section: Observed Productsmentioning
confidence: 99%
“…This loss of water during the reaction is also seen as a negative band in the area around 3200 cm −1 . The loss of different types of free OH groups at the surface is evidenced as a small negative band at 3700 cm −1 (not shown in figure) (Tsyganenko and Mardilovich, 1996). When SO 2 is introduced simultaneously with NO 2 the bands of nitrate are still dominant, especially when the ratio of SO 2 to NO 2 is low, cf.…”
Section: Observed Productsmentioning
confidence: 99%
“…In this arrangement of atoms CN of any O atom is less than or equal to 4 in the bulk alumina, while on a surface it should be 3 or less. 24 Higher coordination number of Cl than oxygen at the surface is an indication of stronger adhesion of Cl on the surface. In a recent study 13 on Cl segregation in TiO 2 also, it was suggested that chlorine is strongly bonded at the TiO 2 surface, which makes it difficult to release it at lower temperatures and therefore it may get entrapped into closed porosity during the densification process.…”
Section: Coordination Numbersmentioning
confidence: 99%
“…After the gold addition the carrier grains were smaller, which can be associated with the disintegration of the agglomerates presented in the beginning and secondly, the partial recrystallization of γ-Al2O3 which could have been possible for a sample calcined at a lower temperature (see Figure 5). In aqueous systems, γ-Al2O3 can again be transformed into aluminum hydroxide or aluminum oxyhydroxide, when the final heat treatment re-creates γ-Al2O3, but with a high specific surface area [35].…”
Section: Semmentioning
confidence: 99%